Volume 2: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 1985
DOI: 10.1115/85-gt-49
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of the Mixing by an Acoustically Pulsed Axisymmetrical Air-Jet

Abstract: The mixing by an acoustically pulsed axisymmetrical air-jet, flowing into the atmosphere, has been studied by means of velocity and temperature profile measurements. The strength of the velocity pulsation imparted to the jet flow and of the associated toroidal vortices were also measured. The entrainment rate was increased by up to two times, with the majority of the extra entrainment occurring over the first five diameters downstream of the jet orifice, where toroidal vortices are formed and attain their grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…Such a result agrees with the numerical results of Jackson et al (1993), who found that flame ignition is always enhanced at high frequencies. It also matches the results of Vermeulen and Yu (1987), who found the strength of the induced vortices approximately increases with frequency. Besides, Vermeulen et al (1992) found that the entrainment coefficient changes faster with pulsation strength at higher frequencies, because the toroidal vortex spacing is less at the greater frequencies.…”
Section: Effect Of Strouhal Numbersupporting
confidence: 90%
See 3 more Smart Citations
“…Such a result agrees with the numerical results of Jackson et al (1993), who found that flame ignition is always enhanced at high frequencies. It also matches the results of Vermeulen and Yu (1987), who found the strength of the induced vortices approximately increases with frequency. Besides, Vermeulen et al (1992) found that the entrainment coefficient changes faster with pulsation strength at higher frequencies, because the toroidal vortex spacing is less at the greater frequencies.…”
Section: Effect Of Strouhal Numbersupporting
confidence: 90%
“…A Nikon digital camera was utilized to record the flame images of 2560 Â 1920 pixels at shutter speeds between 8 and 1=4000 for qualitative comparison. The corresponding parameters of acoustics are Sr ¼ fD f =U f , according to Vermeulen and Yu (1987), and pulsation strength U e =U j ¼ C Â W 0:5 =½U j ðm o j Þ 0:5 , as given by Vermeulen et al (1992a). The linearity between the pulsation strength, U e =U j , and the power number, W 0:5 =½U j ðm o j Þ 0:5 , is given in the correlations by Vermeulen et al (1992a).…”
Section: Combustion Enhancement Of Flares By Excitation 1633mentioning
confidence: 99%
See 2 more Smart Citations
“…The kinetic energy of the primary jet flow is then, Kinetic Energy=l1/2 pjAj(Uj +Ue sin(0)) 3 The average kinetic energy is obtained by integrating the sine wave over a cycle and dividing by 2x which give~s Average Kinetic Energy=1/2 pjAj (uj 3+1 .5Uj~e 2).…”
Section: Recommendationsmentioning
confidence: 99%